Comparison of anterior and posterior surgical approaches in multi-level cervical spondylotic myelopathy - Balakrishnan, Paruvakkattil Kunjan; Abraham, Tinu R.; John, Ajax (International Surgery Journal, 2021)
Background: Cervical spondylotic myelopathy (CSM) is one of the most common dysfunctions of spinal cord which occurs due to degenerative changes in cervical spine disc and facet joints. The management of multilevel spondylotic myelopathy is always controversial. The posterior approaches are always preferable in multiple level spondylosis. But according to newer studies, anterior approaches have similar results. Aim of the study was to compare the efficacy of posterior and anterior approaches in multilevel cervical myelopathy. Methods: This study includes all patients with multilevel cervical spondylotic myelopathy who have undergone decompression surgery with fusion. Detailed preoperative and post-operative assessment was done according to modified Japanese Orthopedic Association scoring system. Results: Eighty eight patients of CSM surgical cases were selected for this study and 29 cases of multi-level CSM were observed. And they were randomly selected for anterior and posterior approaches. Sixteen cases anterior approach was done either ACDF or Corpectomy with fusion. Mean age of study was 51.63 years with 64 males and 24 females. The spinal cord level at which most surgeries did was C5/6, 62 cases. While at level C4/5, it was 49 and at level C3/4 and C6/7, it was 35 and 36 respectively. Conclusions: Both anterior approach and posterior approaches were associated with betterment in postoperative neurological function for multilevel CSM. And there is no significant advantage in doing anterior approach in multilevel CSM.